2008
DOI: 10.1523/jneurosci.3188-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Id2 Is Required for Specification of Dopaminergic Neurons during Adult Olfactory Neurogenesis

Abstract: Understanding the biology of adult neural stem cells has important implications for nervous system development and may contribute to our understanding of neurodegenerative disorders and their treatment. We have characterized the process of olfactory neurogenesis in adult mice lacking inhibitor of DNA binding 2). We found a diminished olfactory bulb containing reduced numbers of granular and periglomerular neurons with a distinct paucity of dopaminergic periglomerular neurons. While no deficiency of the stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 73 publications
3
57
0
Order By: Relevance
“…RNA and cDNA preparation RNA was isolated as described earlier (Havrda et al, 2008). The cDNA was generated using iScript cDNA Synthesis kit (Bio-Rad, Hercules, CA, USA) as per manufacturer's instructions.…”
Section: Microct Evaluation Of Tumor Vasculaturementioning
confidence: 99%
See 1 more Smart Citation
“…RNA and cDNA preparation RNA was isolated as described earlier (Havrda et al, 2008). The cDNA was generated using iScript cDNA Synthesis kit (Bio-Rad, Hercules, CA, USA) as per manufacturer's instructions.…”
Section: Microct Evaluation Of Tumor Vasculaturementioning
confidence: 99%
“…The cDNA was generated using iScript cDNA Synthesis kit (Bio-Rad, Hercules, CA, USA) as per manufacturer's instructions. (Havrda et al, 2008). This primary antibody was replaced by a pre-immune serum in controls.…”
Section: Microct Evaluation Of Tumor Vasculaturementioning
confidence: 99%
“…Indeed, recent studies have shown that Id2 is required for specification of DA neurons during adult olfactory neurogenesis. Sustained Id2 expression mediates olfactory DA neuronal differentiation in migrating neural progenitors in adult animals (Havrda et al, 2008).…”
Section: Diencephalon-enriched Genes In Zebrafish 3375mentioning
confidence: 99%
“…The basic helix-loop-helix family has been studied for its important roles in various physiological and pathophysiological processes, including as transcription factors, in the regulation of neuronal differentiation and even in psychiatric disorders (1)(2)(3)(4)(5)(6). Neuronal Per Arnt Sim domain protein (NPAS) is a member of the basic helix-loop-helix family, which is categorized as Npas1, Npas2, Npas3, and Npas4 (7)(8)(9).…”
mentioning
confidence: 99%